Response of Hard-Bottom Macro-Zoobenthos to the Transition of a Mediterranean Mariculture Fish Plant (Mar Grande of Taranto, Ionian Sea) into an Integrated Multi-Trophic Aquaculture (IMTA) System - Roberta Trani; Cataldo Pierri; Antonella Schiavo; Tamara Lazic; Maria Mercurio; Isabella Coccia; Adriana Giangrande; Caterina Longo (Journal of Marine Science and Engineering)
This study investigates the effects on hard-bottom macro-zoobenthic communities of converting a mariculture plant into an Integrated Multi-Trophic Aquaculture (IMTA) system. This study was conducted from 2018 to 2021 in the semi-enclosed Mar Grande basin of Taranto (northern Ionian Sea), on a facility located 600 m off the coastline, with a production capacity of 100 tons per year of seabass (Dicentrarchus labrax) and seabream (Sparus aurata). The results from seasonal sampling performed in a treatment site, where bioremediators (filter-feeding invertebrates such as sponges, polychaetes, mussels, and macroalgae) were deployed, and a control site without bioremediators were compared. Before the IMTA installation, the hard substrates under the cages were sparsely inhabited, with significant sediment coverage. By 2021, the treatment site exhibited revitalized and more diverse macro-zoobenthic communities, with species richness increasing from 83 taxa in 2018 to 104 taxa, including notable growth in sponges, annelids, mollusks, and bryozoans. In contrast, the control site showed no substantial changes in biodiversity over the same period. Biodiversity indices, including Shannon and Margalef indices, improved significantly at the treatment site, particularly during summer months, highlighting a more resilient and balanced benthic environment. Taxonomic distinctness (delta+) and multivariate analyses (PERMANOVA, PCO) confirmed significant spatial and temporal shifts in community structure at the treatment site, driven by IMTA implementation. SIMPER analysis identified key taxa contributing to these changes, which played a pivotal role in structuring the community. The emergence of filter feeders, predators, and omnivores at the treatment site suggests enhanced nutrient cycling and trophic complexity, while the decline in opportunistic species further supports improved environmental conditions. These findings demonstrate the potential of IMTA to promote recovery and sustainable mariculture practices, also offering a comprehensive understanding of its positive effects on hard-bottom benthic community dynamics.